ANALISIS PENGARUH QUALITY OF WORK LIFE DAN ISLAMIC WORK ETHIC TERHADAP LOYALITAS KARYAWAN MELALUI KINERJA SEBAGAI VARIABEL INTERVENING (STUDI KASUS PADA PT. BANK SYARIAH INDONESIA, TBK KC MEDAN ADAM MALIK) - M. Ilmi Zikri Firdaus; Saparuddin Siregar; Nurlaila Nurlaila; Helma Widya (ITB AAS INDONESIA Surakarta, 2022)
This study aims to determine the effect of Quality of Work Life which is divided into two independent variables, namely Work Participation and Work Environment, as well as another independent variable, namely Islamic Work Ethic at Bank Syariah Indonesia KC Medan Adam Malik. This study uses quantitative methods and associative approaches, data collection techniques using questionnaires and the population and sample in this study were 31 employees at Bank Syariah Indonesia KC Medan Adam Malik using saturated sampling technique. The data obtained were then processed using SPSS Version 25, then analyzed using path analysis. The results of this study indicate that Work Participation on the Work Environment has a correlation value of 0.762 indicating a strong correlation. While the Work Environment on Islamic Work Ethic has a correlation value of 0.535 indicating a moderate correlation. From the results of the Hypothesis Test (First) Work Participation, Work Environment, and Islamic Work Ethic have a significant effect on Employee Performance, this can be seen from the t-count value for the Work Participation variable of 3.162 > t.table 2.051, t-count Work Environment 4.843 > 2.051, and t-count Islamic Work Ethic of 4.162 > t-table 2.051. Meanwhile, from the results of the Hypothesis Test (Second) Work Participation, Work Environment, Islamic Work Ethic, and Employee Performance have a significant effect on Employee Loyalty, this can be seen from the t value for the Work Participation variable of 2.300 > t. table 2.051, t count Work Environment 3.093 > 2.051, t count Islamic Work Ethic of 3.773 > t table 2.051, and t count Employee Performance of 3.681 > t table 2.051. And from the path analysis results show that the Employee Performance variable is not able to strengthen the influence of Work Participation, Work Environment, and Islamic Work Ethic on Employee Loyalty.